Exploring Students’ Experiences on Kampus Mengajar at an Islamic Private University in Yogyakarta - Anjasmara, Sekar; Maharani, Vanessa; Purwanti, Eko; Khoirunnisa, Itsna Zahroh (Universitas Muhammadiyah Yogyakarta, 2024)
Kampus Mengajar is part of the MBKM (Merdeka Belajar Kampus Merdeka) activities, which strives to give students the opportunity and experiences to study and develop outside of the classroom. This program is one of the Ministry of Education and Culture (Kemendikbud) programs to improve the quality of education in Indonesia. In its implementation, Kampus Mengajar is more focused on teaching-learning. To see whether the Kampus Mengajar program is successful in realizing its goals, it is important to know the views of students who participate in the program. The purpose of this study is to explore the experiences of the Kampus Mengajar according to the views of students who participate in the Kampus Mengajar at an Islamic private university. This research is qualitative research with a descriptive qualitative type and was obtained by interviewing several students who studied at one of the private Islamic universities in Yogyakarta. The interviewees who participated in the data were 2 English education students who participated in the Kampus Mengajar activities in 2023. The finding in this research is the experiences of students who participated in Kampus Mengajar, there are different opinions or experiences of each student and the advantages and disadvantages they feel in following the program.